2018
DOI: 10.1080/08927014.2018.1529760
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation into the surface and hydrodynamic characteristics of marine coatings with mimicked hull roughness ranges

Abstract: There are limited scientific data on contributors to the added drag of in-service ships, represented by modern-day coating roughness and biofouling, either separately or combined. This study aimed to gain an insight into roughness and hydrodynamic performance of typical coatings under in-service conditions of roughened ships' hull surfaces. Comprehensive and systematic experimental data on the boundary layer and drag characteristics of antifouling coating systems with different finishes are presented. The coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…As such, studies in relation to hull roughness have been performed using various approaches. Experimental approaches are mainly based on basin experiments using a plate ([4]- [5]). In recent years, there have been an increasing number of studies on ships using numerical simulation methods ([6]- [15]).…”
Section: Introductionmentioning
confidence: 99%
“…As such, studies in relation to hull roughness have been performed using various approaches. Experimental approaches are mainly based on basin experiments using a plate ([4]- [5]). In recent years, there have been an increasing number of studies on ships using numerical simulation methods ([6]- [15]).…”
Section: Introductionmentioning
confidence: 99%
“…Increase in resistance and effective power depending on the type of AF coating and speed. Source: Adapted and modified on the basis of [12].…”
Section: Increase Of Frictional Resistance [%]mentioning
confidence: 99%
“…In all coatings, the aim is to achieve a controlled release of biocide molecules from the polymer matrix (so called binder), while the release mechanisms themselves differ. Although the coating release mechanisms have been elucidated and explained [10][11][12], estimates of total AF biocide emissions from cargo vessels engaged on commercial ocean-going routes are still largely based on the researchers' estimates. Observing several container vessels of various classes (designed in the period from 1990 to 2006), it is clear that the draft of vessels increases the least (given the depth limit on navigation routes and terminals), and that neither the length nor beam increases linearly.…”
Section: Speed [Kn]mentioning
confidence: 99%
“…The findings of this study indicated that the estimations of drag penalties based on well-applied, relatively smooth coating conditions underestimate the importance of hull roughness. 36 Figure 1 shows the schematic of BL test setup used by Yeginbayeva 35 for her experiments. As it can be seen from the schematic drawing, test bed is used, first, to accelerate the flow in the measuring section of the ECT, secondly, to allow the standard UNEW’s flat testing panels (L = 0.6 m and W = 0.22 m) illustrated as red to be fitted on it for BL experiments.…”
Section: Review Of Friction Drag Measurement Facilitiesmentioning
confidence: 99%